Pengaruh Komposisi Media Tanam Serbuk Kayu dan Sekam Padi pada Jamur Tiram Putih - Wening Kusumawardani; Hendra Saputra; Heri Kusnayadi (Indonesian Journal of Applied Science and Technology, 2021)
The aim of this study was to determine the effect of the composition of the planting medium of sawdust and rice husk on white oyster mushroom (Pleorotus ostreatus). The study was conducted using experimental methods, Completely Randomized Design (CRD) consisted of 5 treatments, which each treatment consisted of three replications. The treatments consisted of SP1 = 100% sawdust + 0% rice husk; SP2 = wood powder 75% + rice husk 25%; SP3 = 50% sawdust + 50% rice husk; SP4 = 25% sawdust + 75% rice husk; and SP5 = 0% sawdust + 100% rice husk. Observational data were analyzed using ANOVA at 5% significance level, if the results of data analysis showed significant differences, then further tests were carried out using the Least Significant Difference Test (LSD) at 5% significance level. The results of data analysis showed that the fastest of mycellium spread time was in the SP5, which was 24 days after inoculation. The fastest of pin head appearance time was found in the SP3, which was 88 days after inoculation. The heaviest fruit weight was found in the SP3 treatment and the lowest fruit weight was found in the SP5.